2019
DOI: 10.7150/thno.30658
|View full text |Cite
|
Sign up to set email alerts
|

Progerin accumulation in nucleus pulposus cells impairs mitochondrial function and induces intervertebral disc degeneration and therapeutic effects of sulforaphane

Abstract: Progerin, a truncated unprocessed lamin A protein, causes tissue aging and degeneration. In this study we explored the role of progerin in the pathogenesis of intervertebral disc degeneration (IDD). We also examined the effect of sulforaphane (SFN) on progerin accumulation and mitochondrial dysfunction in IDD. Methods : The role of progerin in IDD was explored using human nucleus pulposus (NP) tissues, rat NP cells, and Lmna G609G knock-in mice. Immunostaining, X-ray imaging, and Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 70 publications
2
80
0
Order By: Relevance
“…30 The mitochondrial apoptosis pathway is induced mainly by apoptotic signals. 31 Apoptotic signals could lead to the loss of MMP, and cause the release of cytochrome c from the mitochondria into the cytosol. 31,32 Bcl-2 family proteins could maintain the mitochondrial integrity, including proapoptotic protein Bax, and anti-apoptotic protein Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The mitochondrial apoptosis pathway is induced mainly by apoptotic signals. 31 Apoptotic signals could lead to the loss of MMP, and cause the release of cytochrome c from the mitochondria into the cytosol. 31,32 Bcl-2 family proteins could maintain the mitochondrial integrity, including proapoptotic protein Bax, and anti-apoptotic protein Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…31 Apoptotic signals could lead to the loss of MMP, and cause the release of cytochrome c from the mitochondria into the cytosol. 31,32 Bcl-2 family proteins could maintain the mitochondrial integrity, including proapoptotic protein Bax, and anti-apoptotic protein Bcl-2. 33 Bax could trigger the release of cytochrome c into the cytosol via regulation of the mitochondrial permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Rat NP cells were kindly generated and donated by Prof. Di Chen (Shenzhen Institutes of Advanced Technology, Chinese Academy of Sciences), and were maintained in DMEM/F12 (1:1) (DF12; Gibco, Grand Island, NY, United States) containing 10% fetal bovine serum (FBS; Invitrogen, Carlsbad, CA, United States) and 1% antibiotics (penicillin/streptomycin) (Gibco) in a 5% CO 2 incubator at 37°C ( Zheng et al, 2018 ; Xu X. et al, 2019 ). The complete culture medium was replaced every other day.…”
Section: Methodsmentioning
confidence: 99%
“…This compound is formed by glucoraphanin in the existence of the myrosinase enzymes. As an active compound, this naturally occurring nutraceutical compound is classified at the isothiocyanate group of organosulfur compounds (Xu et al, ). It seems that the extract of B. oleracea containing sulforaphane has a great anti‐inflammatory potential and significantly improves spatial learning (Subedi, Cho, Park, Choi, & Kim, ).…”
Section: Significant Properties Of Sulforaphanementioning
confidence: 99%
“…It seems that the extract of B. oleracea containing sulforaphane has a great anti‐inflammatory potential and significantly improves spatial learning (Subedi, Cho, Park, Choi, & Kim, ). It has been demonstrated that sulforaphane has the capability of decreasing the mitochondrial dysfunction and improving aging deficiencies (Xu et al, ). In addition to anti‐inflammatory and antiaging effects, sulforaphane has shown a number of other pharmacological potentials such as antidiabetic (Wang et al, ), antioxidant (Subedi et al, ), antitumor (Negrette‐Guzmán, ), hepatoprotection (Saleh, Mansour, Hashad, & Bakeer, ), and cardioprotection (Angeloni et al, ).…”
Section: Significant Properties Of Sulforaphanementioning
confidence: 99%